(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Banking is quickly becoming a global sector with no geographical or territorial borders. The rising number of mergers and acquisitions in the banking business are symptoms of an inorganic growth process. With the growth of global trade, there has been a continuous increase in cross-border mergers. This article makes an attempt to examine banking sector trends as well as the history of mergers and acquisitions in various nations. In this paper discuss the introduction of Indian Banking Sector, and importance of banking, mergers, economic and behavioral theory of merger, rationale for mergers in banking sector, facets of merger activity, reasons of mergers and amalgamations.